Kolkata Port Trust - Bandyopadhyay, Tathagata, (SAGE Knowledge. Cases., 2010)
Kolkata Port (KoPT) had achieved a turnaround from having made a loss of Rs 7.5 crores (cr) in the year 200001 to a net surplus of Rs 465.1 cr in the year 200607. A variety of initiatives had been taken during the intervening years with a focus on tariff rationalization, revenues from alternate sources, infrastructure development and productivity improvements. While these had yielded results, there was a fundamental issue of operational complexity and inability to compete due to the locational disadvantage. KoPT was a riverine port with two dock complexes, 115 kms and 232 kms at Haldia and Kolkata respectively, upstream on the Hooghly, with draft limitations.Two significant studies having implications for future strategies of KoPT had been submitted in March and November 2007. The top management of the port, including the Chairman who was responsible for driving many of the initiatives, was concerned that it won't be possible to achieve a long term sustainable growth continuing with the strategies employed so far. A well thought out future roadmap, breaking away from the present thinking, was essential for sustained growth.